2005
DOI: 10.1002/jbm.a.30368
|View full text |Cite
|
Sign up to set email alerts
|

Effect of synovial fluid, phosphate‐buffered saline solution, and water on the dissolution and corrosion properties of CoCrMo alloys as used in orthopedic implants

Abstract: The corrosion and dissolution of high- and low-carbon CoCrMo alloys, as used in orthopedic joint replacements, were studied by immersing samples in phosphate-buffered saline (PBS), water, and synovial fluid at 37 degrees C for up to 35 days. Bulk properties were analyzed with a fine ion beam microscope. Surface analyses by X-ray photoelectron spectroscopy and Auger electron spectroscopy showed surprisingly that synovial fluid produced a thin oxide/hydroxide layer. Release of ions into solution from the alloy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 24 publications
4
55
0
Order By: Relevance
“…A hydrophobic adsorbed layer from synovial fluid reduces corrosion, and therefore reduces the oxide thickness that protects the bulk metal. A protective layer would explain the observation that synovial fluid produces a significantly thinner oxide layer than PBS after 35 days immersion of the ''as-received'' CoCr alloy, 30 identical to the samples used in the present work.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…A hydrophobic adsorbed layer from synovial fluid reduces corrosion, and therefore reduces the oxide thickness that protects the bulk metal. A protective layer would explain the observation that synovial fluid produces a significantly thinner oxide layer than PBS after 35 days immersion of the ''as-received'' CoCr alloy, 30 identical to the samples used in the present work.…”
Section: Discussionsupporting
confidence: 53%
“…The ToF-SIMS depth profiles demonstrated that deposits of calcium phosphate on the sample surfaces immersed in serum contained Co and Cr ions, supporting the hypothesis that the deposits absorb and reduce the dissolved metals. An organic ligand is present in synovial fluid, which is highly reactive with Cr 3þ , 14,30 increasing the dissolution of Cr in relation to Co. This is reflected in the synovial fluid data in Figure 6 (dissolved Cr), contributing to the upper regression line, which includes EDTA and albumin in PBS and the elevated concentration of the synovial fluid points on Figure 8A.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…These facts could explain the low Co +2 ions release concentration detected in the 10 ml sample solution [52,53]. The media used in this experiment was similar to that used by Karimi [54].…”
Section: Ions Released Rate Comparison Resultsmentioning
confidence: 98%
“…15 Moreover synovial fluid causes corrosion of the bearing surfaces that results in highest concentrations of chromium in the synovial fluid. 16 The natural variation in chromium levels due to exercise 17 and possibly the transient release from the synovial fluid makes this element less suitable to compare wear of bearing surfaces.…”
Section: Discussionmentioning
confidence: 99%